2019
DOI: 10.1016/j.kint.2018.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Deceased-donor acute kidney injury is not associated with kidney allograft failure

Abstract: Deceased-donor acute kidney injury (AKI) is associated with organ discard and delayed graft function, but data on longer-term allograft survival are limited. We performed a multicenter study to determine associations between donor AKI (from none to severe based on AKI Network stages) and all-cause graft failure, adjusting for donor, transplant, and recipient factors. We examined whether any of the following factors modified the relationship between donor AKI and graft survival: kidney donor profile index, cold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
87
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 50 publications
9
87
0
1
Order By: Relevance
“…Historically, donation after cardiac death (DCD) donors and kidneys from donors with acute kidney injury (AKI) were considered independent risk factors for DGF, allograft failure, and inferior outcomes . With increasing experience, however, updated studies have shown good independent outcomes for both DCD and AKI donor kidneys, including those with severe AKI (AKIN stage 2‐3) . Despite this progress, limited data exist on outcomes specific to AKI DCD donor kidneys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Historically, donation after cardiac death (DCD) donors and kidneys from donors with acute kidney injury (AKI) were considered independent risk factors for DGF, allograft failure, and inferior outcomes . With increasing experience, however, updated studies have shown good independent outcomes for both DCD and AKI donor kidneys, including those with severe AKI (AKIN stage 2‐3) . Despite this progress, limited data exist on outcomes specific to AKI DCD donor kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…With growing DCD experience, updated data have shown comparable outcomes between donation after brain death (DBD) and DCD kidneys, including good long‐term graft survival in DCD kidney transplant recipients . Similarly, excellent results, equivalent to those of non‐AKI donors, have been observed in kidney transplants using AKI donors . To date, however, there continues to be limited data on outcomes specific to DCD AKI donors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple single‐center studies have demonstrated that kidneys transplanted from donors with AKI, typically defined as a terminal creatinine ≥2.0 mg/dl, have an increased risk of delayed graft function (DGF), with greater risk of DGF seen with more severe AKI . Despite the increased risk of early complications, these kidneys are associated with excellent allograft survival and allograft function in the short term, even with increasing severity of AKI in the donor [.] However, the majority of kidney transplants included in these studies had cold ischemia time (CIT) <24 h.…”
Section: Introductionmentioning
confidence: 99%
“…This is possibly due to selection bias as only the ‘best’ donor kidneys with very severe AKI were utilized. A more recent publication by Hall provided 3 years recipient outcome data from a large cohort of AKI donors and found no difference in graft survival according to AKI stage, although no donors received RRT . Excellent short‐term graft outcomes were reported in a single centre study which included donors with severe AKI requiring RRT …”
Section: Discussionmentioning
confidence: 99%